2018
DOI: 10.1080/10942912.2018.1508156
|View full text |Cite
|
Sign up to set email alerts
|

Volume estimation of strawberries, mushrooms, and tomatoes with a machine vision system

Abstract: A computer vision technique was used to determine the volume of raw agricultural products with an irregular shape. Thirty images of each rotated raw roma tomato, salad tomato, white button mushroom, and strawberry were collected. Volume determinations of these products using the optical imaging system were compared to volume measurements collected using a water displacement/buoyant force method. A high correlation was found between measurements from both methods. Furthermore, regression analyses of weight and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The authors (Razavi & Parvar, ) have investigated the important physical properties and mechanical characteristics of the kiwi fruit which need to be considered during the design of the system for postharvest operations. The authors (Concha‐Meyer, Eifert, Wang, & Sanglay, ) have used a computer vision system to predict the volume of tomatoes, strawberries, and mushrooms. The study supports that the weight of these agricultural products can be used as a nondestructive way to forecast their volume.…”
Section: Introductionmentioning
confidence: 99%
“…The authors (Razavi & Parvar, ) have investigated the important physical properties and mechanical characteristics of the kiwi fruit which need to be considered during the design of the system for postharvest operations. The authors (Concha‐Meyer, Eifert, Wang, & Sanglay, ) have used a computer vision system to predict the volume of tomatoes, strawberries, and mushrooms. The study supports that the weight of these agricultural products can be used as a nondestructive way to forecast their volume.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they found that the mass, volume, and density of tomato were 24.76 g, 51.62 cm 3 , and 10.96 g/cm 3 , respectively (Onifade & Aregbesola, 2013). Concha‐Meyer, Eifert, Wang, and Sanglay (2018) reported that the weight, volume, and density of tomato was 68.7 g, 72.1cm 3 and 0.95 g/cm 3 , respectively (Concha‐Meyer et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A millimeter electronic digital caliper (GENERAL UPC 22064) was used to measure the dimensions of a whole fruit length, diameter, seed diameter, and seed pocket space diameter (Figure 1). The volume of the whole fruit was measured by water displacement method where, a single fruit was immersed in water in a graduated tube (Concha‐Meyer et al., 2018). The density was determined by dividing the weight of each fruit by its volume.…”
Section: Methodsmentioning
confidence: 99%